PENGARUH SUBSTITUSI TEPUNG KACANG MERAH TERHADAP KUALITAS KULIT PIE - Verawati, Verawati; Ruaida, Ruaida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2015)
Utilization of red beans in the community is still modest. One way to optimizethe use of red beans can be done through the process of flouring. Red bean flour hasa high protein content, but has a low gluten. This is supportive in making the pie. Theuse of flour has a low gluten content, can result in a pie crust with good quality whichis brittle texture. This reseach is to analyze the effect of substitution of red bean flouras much 25% and 50% of the amount of wheat flour for quality of color, fragrance,flavor, and texture of the pie. The research is a true experiment using a completelyrandomized design with three replications and 30 of panellists. The results ofhypothesis tests show there are significant levels in both treatments. In the colorquality, the resulting pie less golden yellow colored. In quality fragrance (fragrantbutter), resulting pie fragrant flavorful enough butter. While the quality of the scent(red bean), pie produced quite flavorful beans. In the texture quality, the resulting piebrittle texture. On the quality of taste (savory) and flavor (red bean), the resulting pieand pretty tasteless savory taste of red beans. Based on the hedonic test, panelistspreferred the substitution of 25% of the 50%.Keywords: red bean flour, pie, pie quality